Семіотичні складові образу Юди Іскаріота (на прикладі творів Лесі Українки, Ольги Кобилянської, Віктора Домонтовича) (Літератури світу: поетика, ментальність і духовність, 2016)
The article under consideration is devoted to the semiotic analyses of the biblical apostle Judah Iscariot. Being one of the most contradictory religious character, the image of Judah Iscariot is the actual subject of research. Our article demonstrates the semiotic paradigm of Judah from different points of view including portrait semiotics (paleness, timitidy, secrecy and slouch), gesture semiotics (abrupt movements)and symbol semiotics (hopelessness, suicide, treason for salvation). The research is stressed on the dualistic nature of Judah’s presentation starting from traditional betrayer and finishing the savior of society. The article’s summary will be used for students learning literary criticism and philologists
Keywords: компаративний метод; семіотика; архетип; семіотика портрету; символізм; дуалізм